APPLYING THE TECHNOLOGY ACCEPTANCE MODEL TO GAUGE UNDERGRADUATE STUDENTS’ PERCEPTIONS OF USING LEARNING MANAGEMENT SYSTEMS IN ENGLISH CLASS - Fauzul Etfita; Marliansyah Marliansyah; Sri Wahyuni; Asnawi Asnawi (STKIP Persada Khatulistiwa Sintang, 2022)
The transmission of covid-19 has challenged the English lecturer to transform the offline learning to entirely online learning. In managing the classroom virtualy, the lecturer utilized learning management system. Hence, this research aimed to figure outthe students’ perception of using the Learning Management System during the COVID-19 Pandemic at second year students of English Language Education FKIP UIR. The Learning Management Systems that used in this research are limited in using of Google Classroom and CERDAS. The indicator of students’ perception to the Learning Management Systems in this research are Usefulness, Ease of Use, Ease of Learning, and Satisfaction. This research usedthe Quantitative method to analyze the data. To collect the data, the reesearchers usedquestionnaire as the instrument of this research. In analyzing the data, the researchers employed the assessment scale. The results for all indicators categorized ‘agree’. Consequently, the study can be implied that the learning and teaching process through LMS can be accessible and useable